2015
DOI: 10.1016/j.pbi.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Plant-mediated ‘apparent effects’ between mycorrhiza and insect herbivores

Abstract: Plants mediate indirect 'apparent' effects between above-ground herbivores and below-ground mutualistic mycorrhizal fungi. The herbivore-plant-mycorrhiza continuum is further complicated because signals produced by plants in response to herbivores can be transmitted to other plants via shared fungal networks below ground. Insect herbivores, such as aphids, probably affect the functioning of mycorrhizal fungi by changing the supply of recent photosynthate from plants to mycorrhizas, whereas there is evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Despite progress on plant interactions with either AM fungi or insects and even tripartite interactions, limited data are available on changes in plant gene expression during AM fungus-plant-insect interactions. Previous reports showed variable effects of AM symbioses on aphids ranging from positive (Gange et al 2002;Babikova et al 2014a;Gilbert and Johnson 2015;Simon et al 2017;Tomczak and Müller 2017) to negative (Guerrieri et al 2004;Babikova et al 2013;Gilbert and Johnson 2015;Tomczak and Müller 2017), or no effects (Gehring and Bennett 2009;Hartley and Gange 2009). A recent study explained that the variation in aphid outcome during a tripartite interaction could be attributed to the changes in plant quality that are driven by the level of AM fungus root colonization as well as plant age (Tomczak and Müller 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite progress on plant interactions with either AM fungi or insects and even tripartite interactions, limited data are available on changes in plant gene expression during AM fungus-plant-insect interactions. Previous reports showed variable effects of AM symbioses on aphids ranging from positive (Gange et al 2002;Babikova et al 2014a;Gilbert and Johnson 2015;Simon et al 2017;Tomczak and Müller 2017) to negative (Guerrieri et al 2004;Babikova et al 2013;Gilbert and Johnson 2015;Tomczak and Müller 2017), or no effects (Gehring and Bennett 2009;Hartley and Gange 2009). A recent study explained that the variation in aphid outcome during a tripartite interaction could be attributed to the changes in plant quality that are driven by the level of AM fungus root colonization as well as plant age (Tomczak and Müller 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Above-ground ecosystems have tended to be considered separate from below-ground ecosystems [172], however there has been recent increased interest in the interaction between soil organisms and above-ground organisms. There is evidence to suggest that fungi may trigger an indirect plant defence response against herbivores, and vice versa [173][174][175][176] since plant defence response to insect predation is not limited to the roots and can result in accumulation of anti-feedant compounds in shoots [126,127] and up-regulation of genes associated with plant defence [177,178]. However, AMF is not entirely selfless in its mechanisms of protection: removal of aboveground biomass by herbivores can suppress AMF by altering the plant carbon allocation due to preferential allocation of carbon to other plant parts rather than plant roots [179].…”
Section: Protection Against Soil and Above-ground Organismsmentioning
confidence: 99%
“…The interactions range from permanent to highly ephemeral. Mycorrhizal fungi, for example, form long-term associations with their host plant, which results in shifts in nutrient acquisition, source–sink dynamics and ultimately plant growth and defence ( Smith and Read 2010 ; Pedone-Bonfim et al 2013 ; Gilbert and Johnson 2015 ; Schweiger and Müller 2015 ). In contrast, mobile leaf-chewing insect herbivores interact with the host plant for only a short period of time and cause transient changes in metabolism that may enhance the defence and tolerance of the host ( Karban and Baldwin 1997 ; Orians et al 2011 ; Schultz et al 2013 ; Robert et al 2014 ; Acevedo et al 2015 ; Zhou et al 2015 ; Johnson et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both ectomycorrhizal and arbuscular mycorrhizal fungi (AMF) provide mineral nutrients to the host plant and also alter the concentrations of both primary and secondary metabolites within the host ( Simon et al 1993 ; Wright et al 1998 ; Pedone-Bonfim et al 2013 ; Gilbert and Johnson 2015 ; Schweiger and Müller 2015 ). Pedone-Bonfim et al (2013) demonstrated that the concentrations of sugars and protein, as well as various phenolics were elevated in mycorrhizal plants.…”
Section: Introductionmentioning
confidence: 99%